2006
DOI: 10.1111/j.1365-2427.2006.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

How wide to cast the net? Cross‐taxon congruence of species richness, community similarity and indicator taxa in ponds

Abstract: 1. Broad-scale assessments of biodiversity often rely on the use of surrogate taxa, whose reliability has rarely been tested, particularly in freshwater systems. Here we use data from 46 ponds in two regions of the U.K. to explore the performance of macroinvertebrate taxa as surrogates for the rapid assessment of pond biodiversity. For the four dominant taxonomic groups in these ponds (Chironomidae, Coleoptera, Gastropoda and Trichoptera) we explore cross-taxon species richness relationships in each of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
116
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 49 publications
10
116
0
2
Order By: Relevance
“…Where strong positive or negative concordance is found, a taxonomic group may be used as surrogate to indicate patterns of other taxonomic groups (Heino 2010;Paavola et al 2003). In spite of its obvious importance, community concordance has been relatively little studied in pond ecosystems (Bilton et al 2006;Landi et al 2012) and especially between fish and amphibian species.…”
Section: Introductionmentioning
confidence: 99%
“…Where strong positive or negative concordance is found, a taxonomic group may be used as surrogate to indicate patterns of other taxonomic groups (Heino 2010;Paavola et al 2003). In spite of its obvious importance, community concordance has been relatively little studied in pond ecosystems (Bilton et al 2006;Landi et al 2012) and especially between fish and amphibian species.…”
Section: Introductionmentioning
confidence: 99%
“…However, the utility of diversity surrogates has been questioned in recent years because correlations of species richness between groups have been found to be highly variable across taxa and regions (e.g., Bilton et al, 2006;Prendergast, 1997). Several studies have suggested that complementary measures, taking other aspects of diversity into account, should be used in order to determine the surrogacy value of a group (Bilton et al, 2006;Su et al, 2004). A recently proposed approach is to look for congruence in community similarity, that is, the similarity in the species composition of the pairs of groups to be compared in different areas (Bilton et al, 2006;Su et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that complementary measures, taking other aspects of diversity into account, should be used in order to determine the surrogacy value of a group (Bilton et al, 2006;Su et al, 2004). A recently proposed approach is to look for congruence in community similarity, that is, the similarity in the species composition of the pairs of groups to be compared in different areas (Bilton et al, 2006;Su et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Within this group of organisms are Coleoptera and Hemiptera, two of the most common groups in these environments. Water beetles are generally considered a suitable group to assess the environmental and conservation value of wetland sites and habitats (Bilton et al, 2006;Davis et al, 1987;Eyre & Rushton, 1989;Eyre et al, 1993;Foster, 1987Foster, , 1999Foster et al, 1990;Oertli et al, 2005;Ribera & Foster, 1992;Sánchez-Fernández et al, 2006). The detailed study of the autoecology of aquatic insects, especially water beetles, has revealed the existence of many species with narrow ecological requirements including adaptations to saline environments (Foster, 2000;Greenwood & Wood, 2002).…”
Section: Introductionmentioning
confidence: 99%